Gavin Douglas, The Palyce of Honour - Douglas, Gawin, 1474?-1522; Parkinson, David John, 1956-; Project Muse. (Kalamazoo, Michigan : Published for TEAMS (Teaching Association for Medieval Studies) in association with the University of Rochester by Medieval Institute Publications, 2018)
"This edition is based on a thorough reconsideration of the earliest complete printing of Douglas's Palyce. It offers a window into the poet's leading concerns: among them, the refinement of form through the interweaving of disparate models and sources; the interplay of entertainment, prophecy, admonition, encomium, and downright foolery; and, under the guise of incompetence and feebleness, the representation of the poet as a sly, acerbic, even visionary commentator on his times and society. Douglas prepares Scottish readers for a new freedom of scope and movement by looking to humanist learning for models for engaging with Classical and Scriptural traditions. He does so with an urgency and immediacy that repays close attention. Designed to replace the 1992 TEAMS Palis of Honoure, this edition has a new, expanded introduction, completely reconsidered text, and thoroughly revised commentary and bibliography"--
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Poetry, Medieval; Scottish poetry -- To 1700.; Poésie écossaise -- Jusqu'à 1700.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Poetry, Medieval; Scottish poetry; To 1700